Women and legal education: Unearthing the gender experiences of female students in law schools - Kundal, Navjeet Sidhu; Singh, Garima (Journal of Interdisciplinary Studies in Education, 2024)
This paper examines the gendered experiences of female students in Indian law schools, highlighting the influence of societal norms and patriarchal expectations on their education and career choices. Despite the growing presence of national universities offering legal education, women continue to face significant challenges rooted in traditional gender roles. These societal pressures often dictate the professions deemed appropriate for women, reinforcing male-dominated norms and limiting their professional autonomy. Through an analysis of the experiences of female law students, this study sheds light on the structural barriers they encounter both within educational institutions and in broader society. The findings emphasize the need for systemic changes at the home, workplace, and societal levels to create a more equitable environment for women pursuing careers in law.